(untitled) (Sociologisk Forskning, 2012)
Integration or illusion – a deviance perspective Denmark experienced one of its most successful periods of economic growth in 2004– 2008 with a tremendous reduction of unemployment, which in June 2008 was around. 1.5 percent, far below the expected level of structural unemployment. In the wake of this development the lack of utilization of migrants’ educations and skills became, once again, a core concern. The political, societal and academic debate followed to a great extent the traditional top-down approach to the problem and revolved around two axes: 1. How effective the labour market was/is to make use of migrants’ skills. 2. Whether there were patterns of over-education as expression of institutional and societal discrimination. The focus of the present study is, however, quite different: We examine the pattern of deviance in relation to labour market participation (not integration), and instead of searching for explanations for the lack of integration, we attempt to identify and explain the deviance pattern as a product of institutionally inherent possibilities and barriers on the one hand and articulating immigrants as rational actors (not victims) on the other. We argue that deviance is not only a more fruitful theoretical and analytical framework than integration and discrimination. Taking departure in empirical evidence on immigrants’ preferences and behaviour as bounded rational actors, and how they actually articulate their everyday life practical experiences, including adjustment of what they want and what they can, the deviance perspective, we believe, also reduces the theoretical and normative biases, that characterises the discrimination and integration framework, and provide more reliable explanations.